Communication from the governor of Virginia transmitting preambles and resolutions adopted by the legislatures of Tennessee and Pennsylvania : January 29, 1861 (Document (Virginia. General Assembly. Senate), 1861)
1861 Tennessee resolution proposing pro-slavery amendments to the United States Constitution (transmitted by Tennessee governor Isham G. Harris) and the Pennsylvania resolutions against the recently passed Ordinance of Secession (transmitted by Pennsylvania governor A. G. Curtin); all were transmitted to Virginia governor John Lechter, who then submitted them to the General Assembly.